Like, Share or Comment ‘Till We Die: Analyzing Football Fans’ Engagements, Identity and Loyalty on Social Media - Sabri Kaya; Metin Argan; Mehpare Tokay Argan (Sport i Turystyka, 2024)
Football clubs have increasingly recognized the importance of social media networks as crucial tools for communication and interaction with their fans, both online and offline. The purpose of this study was to develop an all-encompassing conceptual model that scrutinizes the complex interconnection among fan engagement, team identity, and loyalty on social media channels, with a particular focus on football. Data were collected via an online survey involving 264 avid football fans associated with three prominent clubs in the Turkish Football Super League. The measurement of social media engagement encompassed three sub-dimensions: consumption, contribution, and creation. Hypotheses were tested using exploratory factor analysis, confirmatory factor analysis, and structural equation modeling. The results confirmed four out of seven hypotheses, providing evidence of significant associations between the constructs under investigation. The findings revealed meaningful connections between fan engagement, identification, and loyalty behaviors, such as liking, sharing, and commenting on social media platforms. The findings of this research bear multiple implications that offer significant insights for football managers and sports marketers seeking to enhance fan involvement through the implementation of advanced social media strategies. Furthermore, this study enhances our understanding of social media habits among fans, providing a precious asset for marketing professionals who utilize social media networks in their marketing strategies.